Autologous bone reconstruction as sandwich technique in pediatric posterior fossa surgery: finding a noble eightfold path for developing countries - Singh, Suyash; Bhaisora, Kamlesh Singh; Srivastava, Arun Kumar; Behari, Sanjay (International Surgery Journal, 2019)
Background: Sub-occipital craniotomy in pediatric population is difficult owing to uneven surface of growing calvaria and thin dura. Our novel technique using autologous bone chips and gelfoam bridges the two standard techniques. In this study, we intend to compare the surgical outcome in pediatric posterior fossa tumours. Methods: We included patients, operated via midline sub-occipital approach, from January 2013 to October 2018 and grouped them, on basis of whether or not sandwich reconstruction was done. We compared pseudomeningocele, post-operative headache, CSF leakage and postoperative hydrocephalus requiring CSF diversion. The aesthetic outcome was assessed using Stony Brook scar evaluation scale (SBSES). Results: 124 patients, divided into group A (n=53), group B (n=58) and group C (n=13) based on technique of surgical closure. The sandwich closure is significantly better in terms of both aesthesis and post-operative pain (p<0.05). There was a trend showing that sandwich closure decreases risk for pseudomeningocoele, wound infection, CSF leak and post-operative hydrocephalus. Median SBSES Score in group B was 4 compared to 2 in group A and patients were significantly more satisfied. Conclusions: The uniform bone coverage with sandwich closure provides nearly similar reconstruction to craniotomy. All risks of using drill over pediatric calvaria are eliminated and advantages are carried. The bony barrier prevents adhesion and decreases both immediate and delayed headache. The technique is not only technically easier and aesthetically better, but also has better long term satisfactory results with possibility of neo-bone formation.